Pengaruh ekstrak temulawak (Curcuma xanthorrhiza) terhadap kerusakan sel usus halus mencit (Mus musculus) yang diinduksi Piroxicam - Moch. Haikal; Septiana Kurniasari (Universitas Sultan Ageng Tirtayasa, 2021)
Piroxicam is a non-steroidal anti-inflammatory drug (NSAID) widely used as an analgesic and anti-inflammatory in rheumatoid arthritis, osteoarthritis. However, Piroxicam can cause gastrointestinal side effects and peptic ulcers when given orally. Piroxicam can also cause cholestasis. Also, if Piroxicam is used continuously in high doses, it can cause damage to the small intestine. A compound can minimize small intestinal cell damage called an antioxidant. This study aims to analyze the effect of curcumin extract (Curcuma xanthorrhiza) on Piroxicam-induced damage to mice's small intestinal cells (Mus musculus). This study used 80 male mice and divided into 3 groups, namely negative control (K-), negative Piroxicam (P-) and positive Piroxicam (P +). Giving ginger extract given orally at a dose of 1.4 gr / kgBW; 2.0 gr / kgBW; 2.6 gr / kgBW; 3.2 g / kg BW and 3.8 g / kg BW, while the Piroxicam dosage used was 10 mg / kg BW and 30 mg / kg BW. The results showed that the more Piroxicam doses were given, the higher the level of small intestinal cell damage. Along with increasing the dosage of ginger extract, the level of damage to small intestinal cells is reduced.